A CHANDRA OBSERVATION OF THE BURSTING MILLISECOND X-RAY PULSAR IGR J17511-3057 - Paizis, Adamantia; Nowak, M. A.; Rodriguez, Jerome; Wilms, Jörn; Chaty, Sylvain; Del Santo, Melania; Ubertini, P. (Astrophysical Journal, 2012)
IGR J17511-3057 is a low-mass X-ray binary hosting a neutron star and is one of the few accreting millisecond X-ray pulsars with X-ray bursts. We report on a 20 ks Chandra grating observation of IGR J17511-3057, performed on 2009 September 22. We determine the most accurate X-ray position of IGRJ17511-3057, alpha(J2000) = 17(h)51(m)08(s).66, delta(J2000) = -30 degrees.57'41 ''.0 (90% uncertainty of 0 ''.6). During the observation, a similar to 54 s long type-I X-ray burst is detected. The persistent (non-burst) emission has an absorbed 0.5-8 keV luminosity of 1.7 x 10(36) erg s(-1) (at 6.9 kpc) and can be well described by a thermal Comptonization model of soft, similar to 0.6 keV, seed photons upscattered by a hot corona. The type-I X-ray burst spectrum, with average luminosity over the 54 s duration L0.5-8 (keV) = 1.6 x 10(37) erg s(-1), can be well described by a blackbody with kT(bb) similar to 1.6 keV and R-bb similar to 5 km. While an evolution in temperature of the blackbody can be appreciated throughout the burst (average peak kT(bb) = 2.5(-0.4)(+0.8) keV to tail kT(bb) = 1.3(-0.1)(+0.2) keV), the relative emitting surface shows no evolution. The overall persistent and type-I burst properties observed during the Chandra observation are consistent with what was previously reported during the 2009 outburst of IGR J17511-3057.
Keywords: accretion; accretion disks; pulsars: individual (IGR J17511-3057); stars: neutron; X-rays: binaries; X-rays: bursts